Effective Academic Performance Assessment in Children with Autism Spectrum Disorders - Pereverzeva D.S; Braginets E.I; Tyushkevich S.A; Gorbachevskaya N.L (Moscow State University of Psychology and Education, 2020)
The article is dedicated to the problem of academic skills assessment in children with autism spectrum disorders (ASD) participating in the Adapted Educational Programmes 8.1 and 8.2. Implementation of inclusive education raises a question of academic assessment and test accommodation design for students with special needs. We provide a description of an approach called the 'Universal Design of Assessment' and analyse the main features of cognitive and social development in children with ASD which have to be accounted for in the educational process. We then discuss the International Performance Indicators in Primary Schools (iPIPS) and its modification for children with ASD developed according to their special needs. A brief outline of research results shows that the modification of the iPIPS technique does not affect the measured construct. Finally, we provide some recommendations on how to apply the technique depending on the students' individual features.